Pulsed electric fields: a sharp sword in the battle against cancers - Zhang, Lu; Dong, Shoulong; Teng, Fei; Wang, Yuan; Xu, Wei; Chen, Yang; Yu, Liang; Yao, Chenguo; Wang, Zhiqiang (Frontiers in Immunology, 2025)
Cancer remains a significant threat to human health, and conventional treatments such as surgery, chemotherapy, and radiotherapy have their limitations. In recent years, pulsed electric fields (PEFs) has garnered attention as an emerging method for cancer treatment. It primarily utilizes high-intensity pulse electric fields applied to tumor cells, inducing effects such as electroporation or internal electrical processing, which lead to cell death. This review will introduce the principles of PEFs, its application fields, and its prospects in cancer treatment, aiming to provide readers with a comprehensive understanding of the research areas related to PEFs and cancer therapy.